Technology dissemination in training and manufacture of simple fertilizer equipment - Iswanto Suwarno; Raudatul Innayah; Nabila Turahma Niah Butarbutar; Robbi Rahim; Nia Maharani Raharja; Siewe Pougoue E.B.; Virro I.; Claudia Ann Rutland (Peneliti Teknologi Teknik Indonesia, 2023)
Padukuhan Gadingan is an area on the slopes of Mount Merapi, precisely in the Argomulyo village, Kapanewon Cangkringan, Sleman. Padukuhan Gadingan has very large and fertile land so that most of the population works as farmers. In our project here, we want to conduct training on making a fertilizer sprinkler that makes it easier for farmers to spread fertilizer, the name of the tool is a simple fertilizer sprinkler. Many farmers are elderly and prone to illness, there are still many farmers who fertilize manually without using tools and there is a need for innovative tools to help farmers make their work more effective in agriculture. The aim is to increase farmers' knowledge and understanding of new innovations, utilizing simple tools that do not require large costs to assist the process of fertilizing plants. The methods used are socialization, training, and face-to-face mentoring and the results foster knowledge and insight to the target audience, namely farmer groups in the Gadingan hamlet, especially elderly farmers.